Perilaku Temperatur Minyak Lumas Pada Kapal - Andi Hendrawan; Aris Sasongko Dwiono; Sri Pramono (Dinamika Bahari, 2022)
Lubrication is an important thing in ship machining operations because it becomes a protective layer to separate two surfaces that are in contact with each other with three phases of objects whose volume remains at a constant temperature and pressure. Lubrication serves to prevent friction between components so that it becomes smoother. If the engine is at a high temperature, the oil viscosity will tend to decrease. The more often the lubricant is used, the thing that happens is that the temperature of the lubricating oil varies. The purpose of this study is to describe the behavior of the lubrication temperature on the ship. The research uses quantitative methods by observing the temperature of the main engine along the way by looking at indicators and direct measurements on the main engine using a thermocouple. The results showed that the temperature behavior is very dependent on the age of the lubrication and the operation of the cooling system on the ship's machining system. This study concludes that the lubrication temperature behavior is very dynamic and the influencing factors include the age of the lubrication, the type of lubricant and the engine, as well as the cooling performance.